Strategi Indonesia dalam Mencapai Blue Economy Roadmap Melalui National Blue Agenda Actions Partnership (NBAAP) - Nur Ainun Musdalifah; Darwis Darwis; Imam Fadhil Nugraha (Student Scientific Creativity Journal, 2024)
The blue economy concept is very suitable for island countries with abundant biodiversity. Blue economy prioritizes ecosystem sustainability with marine resources as the main subject. Indonesia sees this concept as an opportunity to utilize its potential through the launch of the Indonesia blue economy roadmap. The Indonesia blue economy roadmap is a very complex design and the challenges ahead are very risky to the goals to be achieved. The international partnership strategy is one of Indonesia’s steps in achieving the goals of the Indonesia blue economy roadmap. The partnership strategy is known as the National Blue Agenda Actions Partnership (NBAAP). This research uses qualitative research methods with library research data collection techniques to see NBAAP as a partnership strategy to support the achievement of the Indonesia blue economy roadmap. The results of the research will discuss the priority sectors of the Indonesia blue economy roadmap, the challenges and problems of the sector, the pillars in the NBAAP partnership strategy, and the NBAAP Program that supports the Indonesia blue economy roadmap. With this in-depth understanding, it is expected that Indonesia’s international partnership strategy in the blue economy can support the achievement of the goals in the Indonesia blue economy roadmap.